Karangkates Railway Tunnel Risk Analysis Based on Ground Penetrating Radar Data - Abdul Aziz Afif; Wiyono; Abu Bakar Sambah (Universitas Pendidikan Ganesha, 2023)
The Karangkates railway tunnel in Malang Regency is more than half a century old and has undergone land use changes into settlements and highways. This study aims to identify cavities between the ground surface and the roof of the Karangkates tunnel using Ground Penetrating Radar (GPR) data. Primary data were obtained through GPR measurements and interviews with residents. Qualitative methods are used to analyze GPR interpretation data readings and risk analysis. Risk analysis is carried out to determine the location and area of cavities and compile long-term risk management. From the results of the GPR analysis, 6 points were found with protruding cavities, with a cavity depth between 8 to 13.4 meters. The location of such cavities is in residential areas and highways. Risk management measures appropriate to the analysis and observation of the research site are carried out to reduce the impact of risk. The results showed that the risk value was low. By implication, appropriate corrective and maintenance actions must be taken to mitigate risks and maintain public safety.